A Security Perspective on Adoption and Migration to Mobile Cloud Technology - Mohammad Bin Ghudayyer; Yasir Javed; Mamdouh Alenezi (JOIV : International Journal on Informatics Visualization, 2017)
Security is one of the main concerns of those who want to adopt and migrate to cloud computing technology. Security issues raised by cloud technology reveals that mobile cloud computing is raising the privacy and security issues such as identification and authentication issue, as sometimes the identity and the authentication of the owner of the device or the owner of the data contained in the cloud was not strictly remote. These are some examples that could be considered as major setbacks to the mobile cloud computing adaptation and the reason why some entities are still reluctant of embracing, adopting and migrating to this technology. This research reviews the phenomenon of mobile cloud computing, and the security and privacy issues intrinsic within the area of mobile application and cloud computing with more emphasis on the security and privacy considerations to embrace and migrate to Mobile Cloud Computing.